2016
DOI: 10.5455/tjfmpc.198970
|View full text |Cite
|
Sign up to set email alerts
|

Active Teaching and Learning Strategies in Medical Education: Perception and Barriers among Faculty Members at Oman Medical College,Sohar/Bowshar Sultanate of Oman

Abstract: Background: Medical education is constantly evolving .It is more effective and long lasting if it is self-initiated and self-directed. Active teaching and learning strategy (ATLS) is the process by which a medical student independently, or in a group, identifies his or her learning objectives and actively seeks information necessary to achieve objectives. The study aims at identifying the faculty's use of active teaching and learning strategies and to explore the perceived barriers to its use in undergraduate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…There is no literature on TBL being used in medical ethics courses. A study conducted at the College of Medicine and Health Sciences (erstwhile Oman Medical College), National University of Science and Technology, (COMHS, NUST) Sultanate of Oman concluded that faculty members are interested in employing active teachinglearning strategies for their courses, but were unable to do so due to the lack of necessary class time, high comfort level with traditional lectures and paucity of time to develop materials (23).…”
Section: Introductionmentioning
confidence: 99%
“…There is no literature on TBL being used in medical ethics courses. A study conducted at the College of Medicine and Health Sciences (erstwhile Oman Medical College), National University of Science and Technology, (COMHS, NUST) Sultanate of Oman concluded that faculty members are interested in employing active teachinglearning strategies for their courses, but were unable to do so due to the lack of necessary class time, high comfort level with traditional lectures and paucity of time to develop materials (23).…”
Section: Introductionmentioning
confidence: 99%